Amniotic Fluid Analysis at Birth as a Predictor of Canine Neonatal Survival - Reddy, Yeddula Venkata Pridhvidhar; Jayakumar, Chopile; Harshan, Hiron Mooloor; Simon, Shibu; Nair, Sreeranjini Aray ikaravattu Raghavan; Sukumaran, Sajitha Indira (The Indian Journal of Animal Reproduction, 2024)
Establishing dependable indicators for neonatal survival is essential in canine practice. Historically, amniotic fluid has  not received attention as a diagnostic tool in dogs. This study analyzed amniotic fluid obtained at whelping from 36  dogs that underwent elective caesarean section (CS) at term to evaluate its potential as a predictor of neonatal survival.  Glucose and cortisol concentrations in amniotic fluid were measured at birth in 72 puppies delivered by elective CS.  These biochemical parameters were subsequently analyzed to relate puppy survival at birth and neonatal viability, as  assessed by APGAR scoring, and to neonatal mortality. The results revealed that stillborn puppies exhibited significantly  higher (p
Keywords: Amniotic Fluid; Glucose; Cortisol; APGAR Scores; Neonatal Survivability